2020
DOI: 10.1042/bsr20192226
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PARP inhibitors as the maintenance therapy in ovarian cancer: a meta-analysis of nine randomized controlled trials

Abstract: Purpose: Poly ADP ribose polymerase (PARP) inhibitors can effectively kill cancer cells by restraining the activity of DNA repair enzymes and utilizing the characteristics of BRCA mutations. This article evaluates the efficacy and safety of PARP inhibitors (PARPis) in the maintenance treatment of ovarian cancer. Method: We searched for clinical trials in electronic databases. PARPis efficacy were evaluated by the hazard ratios (HR) and its 95% confidence intervals (95% CI) of overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Given the deeply researching of molecular pathways found to be dysregulated during the multistep process of oncogenesis, many therapeutic targets have been identified and gave significant results in the clinical practice, which driven the management of cancer into individualized treatments. Poly(ADP-ribose) polymerase inhibitors are one of new personalized treatments for patients with high-grade serous ovarian cancer and demonstrate a high survival advantage in several randomized controlled trials (RCTs) and meta-analyses ( 3 6 ). The treatment modality is based on the mechanisms of “synthetic lethal” and “PARP trapping”, especially for patients with homologous recombination deficiencies (HRD) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the deeply researching of molecular pathways found to be dysregulated during the multistep process of oncogenesis, many therapeutic targets have been identified and gave significant results in the clinical practice, which driven the management of cancer into individualized treatments. Poly(ADP-ribose) polymerase inhibitors are one of new personalized treatments for patients with high-grade serous ovarian cancer and demonstrate a high survival advantage in several randomized controlled trials (RCTs) and meta-analyses ( 3 6 ). The treatment modality is based on the mechanisms of “synthetic lethal” and “PARP trapping”, especially for patients with homologous recombination deficiencies (HRD) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, all PARP inhibitors have never been compared with each other because of the lack of head-to-head trials. Although recent traditional meta-analyses have been published on PARP inhibitors as maintenance treatment in platinum sensitive ROC ( 3 6 ), comparisons among the three drugs were little explored because of the limitation of traditional meta-analysis methods which is based on direct evidence ( 9 ). Thus, the comparative efficacy and safety of FDA-approved PARP inhibitors as maintenance treatment in platinum sensitive ROC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the discovery of a link between BRCA mutations and other types of cancer increased the relevance of this class of drugs beyond ovarian and breast cancer. However, not every patient with a BRCA mutation is sensitive to PARP inhibition, and there are patients with a BRCAwt status that show improvement with these drugs [79]. BRCA mutant tumors may have other genetic alterations that allow proficient HRR; whereas BRCAwt tumors may have mutations in the HRR pathway becoming sensitive to PARPi [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even though PARPi are generally considered as a safer treatment option when compared to other alternatives, these drugs are associated with an increased risk of grade ≥3 side effects [79,81,82]. Therefore, there is need for a functional test that allows for the characterization of a tumor's response to different treatment options, revealing not only cell intrinsic, but also TME-associated features in an assay independent of the genetic makeup/mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis by Shao et al 25 demonstrated that PARPis can significantly improve PFS in ovarian cancer patients. However, they did not evaluate the efficacy in newly diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%